Gold-catalyzed regioselective oxidation of terminal allenes: formation of α-methanesulfonyloxy methyl ketones - Yingdong Luo; Guozhu Zhang; Erik S. Hwang; Thomas A. Wilcoxon; Liming Zhang (Beilstein Journal of Organic Chemistry, 2011)
Synthetically useful α-methanesulfonyloxy methyl ketones are readily prepared in one-step from terminal allenes in fair to good yields. The chemistry relies on a gold-catalyzed intermolecular oxidation of the 1,2-diene unit using 3,5-dichloropyridine N-oxide as the oxidant. The reaction tolerates a range of functional groups and shows excellent regioselectivity.